1993
DOI: 10.1017/s0033291700028452
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic advantage of bifrontal electrode placement in ECT

Abstract: SynopsisFifty-nine patients suffering from a major depressive episode, for whom electroconvulsive therapy (ECT) was clinically indicated, were randomly assigned to one of three electrode placement groups for treatment with brief pulse, threshold-level ECT: bitemporal (BT), right unilateral (RU) or bifrontal (BF). Comparison of these groups in terms of number of treatments, duration of treatment, or incidence of treatment failure, showed that the bilateral placements were superior to the unilateral; comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
4

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 27 publications
2
54
1
4
Order By: Relevance
“…Both were considerably more effective than either low-or moderate-dosage RUL ECT. These findings confirm earlier reports that the efficacy of RUL ECT is influenced by electrical dosage, 5,[14][15][16][17] and that fixed high-dosage RUL ECT can be as effective as BL ECT. 15 Specifically, this study indicates that, at sufficiently high stimulus intensity above the threshold, RUL matches BL ECT in efficacy.…”
Section: Commentsupporting
confidence: 91%
See 1 more Smart Citation
“…Both were considerably more effective than either low-or moderate-dosage RUL ECT. These findings confirm earlier reports that the efficacy of RUL ECT is influenced by electrical dosage, 5,[14][15][16][17] and that fixed high-dosage RUL ECT can be as effective as BL ECT. 15 Specifically, this study indicates that, at sufficiently high stimulus intensity above the threshold, RUL matches BL ECT in efficacy.…”
Section: Commentsupporting
confidence: 91%
“…5,[14][15][16][17] In a 4-group study randomizing patients to RUL and BL placement and to an electrical dosage just above (0%) or 150% above the initial seizure threshold, we found that higher-dosage RUL ECT was considerably more effective than lowdosage RUL ECT and produced less severe cognitive effects than either form of BL ECT. 5 Nonetheless, the higherdosage RUL ECT did not match the efficacy of either type of BL ECT.…”
Section: Arch Genmentioning
confidence: 99%
“…Based on the results of randomized controlled trials (RCTs) comparing real ECT with sham ECT (that is, the repeated administration of anesthesia alone), it is well established that a generalized tonic-clonic seizure is necessary for ECT to exert its antidepressant effect (1). However, several studies have demonstrated that, while eliciting a generalized seizure is sufficient for the efficacy of bilateral ECT, this is not the case for RUL treatment (14)(15)(16)(17). In a landmark study, Sackeim and others (14) found that RUL ECT administered at either low-dose (that is, just above the determined seizure threshold) or moderate-dose (that is, 2.5 times seizure threshold) was significantly less effective than either of these doses of bitemporal ECT.…”
Section: Optimizing Ect Efficacymentioning
confidence: 99%
“…A recent review found that 62% of a sample of 659 elderly patients given ECT had a good outcome, and a further 21% derived some benefit [17], These studies were naturalistic and, therefore, rather better representative than controlled clinical trials of antidepressants although ad mittedly they did not benefit from the pres ence of a randomly assigned comparison group. A number of specific techniques have recently been advocated to increase the 'effi ciency' of ECT [18,19]. These deserve full evaluation in the elderly.…”
Section: Treatmentmentioning
confidence: 99%